2007
DOI: 10.1155/2007/70876
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusand MRSA Colonization Rates among Gravidas Admitted to Labor and Delivery: A Pilot Study

Abstract: Objective. To determine colonization rates of Staphylococcus aureus given the potential for future intervention trials aimed at reducing surgical-site infectious morbidity, and to estimate methicillin-resistant Staphylococcus aureus (MRSA) rates in our patient population. Study design. Prospective pilot investigation comprising data from 104 gravidas admitted to an urban labor and delivery unit. All underwent anterior nares culture collection with a subset also undergoing vaginal culture collection. Results. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 12 publications
2
43
0
2
Order By: Relevance
“…A study in Cleveland, OH, demonstrated a 2.1% prevalence of nasal or vaginal colonization with MRSA among 96 women admitted to a labor and delivery unit; one woman had MRSA colonization at both sites. There was no association between neonatal infection and maternal colonization with S. aureus (54).…”
Section: Neonatal Mrsa Infections and Maternal Colonization And Infecmentioning
confidence: 75%
“…A study in Cleveland, OH, demonstrated a 2.1% prevalence of nasal or vaginal colonization with MRSA among 96 women admitted to a labor and delivery unit; one woman had MRSA colonization at both sites. There was no association between neonatal infection and maternal colonization with S. aureus (54).…”
Section: Neonatal Mrsa Infections and Maternal Colonization And Infecmentioning
confidence: 75%
“…S. aureus has been reported to colonize the vagina in 4 to 22% of pregnant women (2,4,9,13,14). In 2005, following an outbreak of USA300 in postpartum women at our medical center (Columbia University Medical Center), we determined that the prevalence of methicillinsusceptible S. aureus (MSSA) anovaginal colonization was 16.6% and the prevalence of MRSA colonization was 0.5% (9).…”
mentioning
confidence: 99%
“…Postprep samples were taken via swabbing the nares at 1 h, 6 h, and 12 h. Baseline samples were taken prior to the application of prep or saline. The mean baseline level of S. aureus in subjects included in this study was log 10 formulations or mupirocin ointment (2%) for 5 min at room temperature (RT), followed by 15-min incubation at 37°C. Explants were then washed with sterile PBS containing 2% mucin.…”
Section: Discussionmentioning
confidence: 99%
“…aureus colonizes the anterior nares, skin, and mucosal surfaces of approximately 30% of the population (8)(9)(10). Nasal colonization with S. aureus is a well-known risk factor for acquisition of SSIs (11)(12)(13).…”
mentioning
confidence: 99%